Home learning environments and children’s language and literacy skills: a meta-analytic review of studies conducted in low- and middle-income countries - Nag, S; Vagh, SB; Dulay, KM; Snowling, M; Donolato, E; Melby-Lervåg, M (American Psychological Association, 2023)
A robust finding from research in high-income countries is that children living in resource-poor homes are vulnerable to difficulties with language and literacy but less is known about this association in low- and middle-income (LMI) countries. We present a meta-analysis of 6,678 correlations from studies in 43 LMI countries. Overall, the results indicate a small but significant association (r = .08) between home language and literacy environment and children’s language and literacy skills. After examining a range of moderators, adult literacy practices and books-at-home had a significantly larger association with children’s language and literacy skills than did home tutoring. Studies using customized measures demonstrated a more marked association between home attributes and children’s outcomes (r = .14) than studies using a common measure across multiple sites (r = .06). Published studies showed significantly larger associations than unpublished studies, and countries with greater income inequality showed a larger association than relatively egalitarian societies. We conclude that the small overall association should not be taken as support for the absence of, or a vanishingly small relationship between the home learning environment and children’s language and literacy skills in LMI countries. Rather, an important factor in detecting this relationship is that assessments must better reflect the nature of homes in different cultures to capture true variation in the population. Such contextually situated measurement would lead to an inclusive conceptualization of home learning environments and can better inform intervention programs to enhance children’s educational success, a critical target for many LMI countries.